The new Hume debate - Read, Rupert J., 1966-; Richman, Kenneth, 1966- (Routledge, 2000)
Includes new essays by renowned philosophers and Hume scholars such as Barry Stround, Simon Blackburn and Galen Strawson, this is the first book to discuss the whole debate about whether Hume was indeed a sceptic.